Evidence for hydrogen oxidation and metabolic plasticity in widespread deep-sea sulfur-oxidizing bacteria - Anantharaman, Karthik (National Academy of Sciences, 2013)
Hydrothermal vents are a well-known source of energy that powers chemosynthesis in the deep sea. Recent work suggests that microbial chemosynthesis is also surprisingly pervasive throughout the dark oceans, serving as a significant CO(2) sink even at sites far removed from vents. Ammonia and sulfur have been identified as potential electron donors for this chemosynthesis, but they do not fully account for measured rates of dark primary production in the pelagic water column. Here we use metagenomic and metatranscriptomic analyses to show that deep-sea populations of the SUP05 group of uncultured sulfur-oxidizing Gammaproteobacteria, which are abundant in widespread and diverse marine environments, contain and highly express genes encoding group 1 Ni, Fe hydrogenase enzymes for H(2) oxidation. Reconstruction of near-complete genomes of two cooccurring SUP05 populations in hydrothermal plumes and deep waters of the Gulf of California enabled detailed population-specific metatranscriptomic analyses, revealing dynamic patterns of gene content and transcript abundance. SUP05 transcripts for genes involved in H(2) and sulfur oxidation are most abundant in hydrothermal plumes where these electron donors are enriched. In contrast, a second hydrogenase has more abundant transcripts in background deep-sea samples. Coupled with results from a bioenergetic model that suggest that H(2) oxidation can contribute significantly to the SUP05 energy budget, these findings reveal the potential importance of H(2) as a key energy source in the deep ocean. This study also highlights the genomic plasticity of SUP05, which enables this widely distributed group to optimize its energy metabolism (electron donor and acceptor) to local geochemical conditions.